Postmenopausal vaginal atrophy: evaluation of treatment with local estrogen therapy - Minkin MJ; Maamari R; Reiter S (Dove Medical Press, 2014)
Minkin MJ, Maamari R, Reiter S. Int J Womens Health. 2014;6:281–288. On page 281, the year of publication was incorrectly listed as 2013, it should have been 2014. The year for the copyright notice was also listed as 2013 in error, the correct notice is © 2014 Minkin et al. This work is published by Dove Medical Press Limited, and licensed under Creative Commons Attribution – Non Commercial (unported, v3.0) License. The full terms of the License are available at http://creativecommons.org/licenses/by-nc/3.0/. Non-commercial uses of the work are permitted without any further permission from Dove Medical Press Limited, provided the work is properly attributed. Permissions beyond the scope of the License are administered by Dove Medical Press Limited. Information on how to request permission may be found at: http://www.dovepress.com/permissions.php.Read the original article